Memobilisasi Modal untuk Melawan Perampasan Tanah oleh Negara di Persil IV, Sumatera Utara, Indonesia - Linda Elida; Ahmad Sayyidulhaq Arrobbani Lubis; Ahmad Taufan Damanik (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Agrarian conflicts in Indonesia are shaped by persistent inequalities in land access and control, where the state, through legal frameworks and state-owned enterprises, plays a central role in legitimizing dispossession. This study examines how rural communities mobilize different forms of capital to resist state-led land grabbing in Persil IV, North Sumatra. Drawing on Pierre Bourdieu’s theory of capital, the analysis focuses on how economic, social, cultural, and symbolic resources are strategically deployed to sustain collective resistance. Using a qualitative case study approach, data were collected through in-depth interviews with community members, local leaders, and activists involved in the conflict, complemented by field observations and analysis of legal and historical documents, and analyzed through an iterative thematic coding process. The study draws on empirical material generated from prolonged engagement in the field to identify three interrelated dynamics of resistance. First, economic capital supports the financing of legal action and collective mobilization, as reflected in community practices of pooling resources and personal asset sacrifice to sustain litigation and reclaiming activities. Second, social capital expressed through internal solidarity and external alliances strengthens organizational capacity and expands advocacy networks, including collaboration with student groups and non-governmental organizations. Third, cultural and symbolic capital articulated through historical narratives, legal documents, and moral claims generate legitimacy and reinforce community claims to land, particularly through the continued use of cultivation permits and everyday land occupation practices. However, the findings also show that these forms of capital operate within a structurally unequal field, where legal uncertainty, coercive pressure, and institutional bias limit their effectiveness. While communities are able to sustain resistance over time, their capacity to secure definitive land rights remains constrained by the dominance of state and corporate actors. This study contributes to agrarian political economy and rural sociology by providing an empirically grounded account of how capital is mobilized, combined, and constrained in a prolonged agrarian conflict, showing that resistance is sustained not only through material resources but through socially embedded practices shaped by unequal power relations.